Prediction of BLEVE loading on a rigid structure - Wang, Yang; Hao, Hong; Chen, Wensu; Li, J.; Wang, Zitong (2023)
Boiling Liquid Expanding Vapour Explosion (BLEVE) in open space has been investigated in the authors’ previous study. However, for designing structures against BLEVE event, BLEVE load acting on structures, instead of the pressure in open space, should be used in the structural response analysis. Therefore, further study is required to accurately predict BLEVE loads on structures. In this study, 1300 sets of BLEVE cases consisting of 650 wave propagation in open space and 650 pressure wave-structure interaction cases are numerically modelled. The open space BLEVE pressure and reflected pressure waves from the rigid structure are simulated, and the corresponding impulses are calculated. The reflection coefficient chart is developed to predict the reflected BLEVE overpressure on the rigid structure. The diffraction and clearing effects on the reflected waves are analysed with respect to the dimensions of the structure. An empirical formula for predicting the reflected impulse is also proposed. The results obtained in this study can be used together with the open space BLEVE pressure predictions presented by the authors in a previous study to predict the BLEVE loads on structures.